Microcredit and poverty alleviation in Nigeria in COVID-19 pandemic (2021)
Microcredit is a financial service whose importance is often understated. When lack of access to microcredit is exacerbated by a public health emergency such as the COVID-19 pandemic, its real significance as an essential service in poverty alleviation becomes more apparent. The outbreak and spread of the novel coronavirus (COVID-19) has led to dramatic transformations of every sector of the Nigerian society including microcredit delivery system, where formal and informal actors co-exist often in an uneasy relationship. Unfortunately, strategies for inclusive microcredit delivery before and during the COVID-19 pandemic are lacking in Nigeria, fuelling the further exclusion of informal sector in microcredit governance and policy process in Nigeria. The paper reviews the state of the COVID-19 pandemic in Nigeria and identifies policy gaps in microcredit delivery and governance mechanism. The study also highlights the linkages between COVID-19 and microcredit in poverty alleviation with a view to catalyzing increased and inclusive access to microcredit and sustainability policy in Nigeria. It is argued that acknowledging the role of microcredit in informal economy and poverty alleviation is the critical first step towards framing a sustainable microcredit policy in which primary stakeholders are involved.